Effectiveness of Key Biodiversity Areas in representing global avian diversity - Tom P. Lansley; Olivia Crowe; Stuart H. M. Butchart; David P. Edwards; Gavin H. Thomas (Conservation Biology, 2025)
Key Biodiversity Areas (KBAs) are the largest and most complete network of significant sites for the global persistence of biodiversity. Although important sites for birds worldwide have been relatively well assessed, a key question is how effectively the global KBA network represents avian diversity. We identified bird species, orders, habitats, and geographic regions that are underrepresented by KBAs. Area of Habitat (AOH) maps for 10,517 terrestrial bird species were cropped and masked by the extent of each KBA. Almost all species had at least one part of their seasonal distribution in one or more KBAs. Twenty‐nine species had no habitat overlap with KBAs, and 1900 species had 2 ). Terrestrial bird species of tropical forests were 12.8% better represented in KBAs than expected by chance, whereas boreal and temperate forest species were less well represented than expected by chance (74.4% and 25.1%, respectively). Among avian orders, Anseriformes and Charadriiformes were underrepresented in KBAs (29.0% and 17.9%, respectively), whereas Trogoniformes and Psittaciformes were better represented (16.2% and 6.9%, respectively) than expected by chance. Bird species for potential KBA identification include marsh antwren ( Formicivora paludicola ) and Tabar pitta ( Erythropitta splendida ). These are mainly due to recent changes in species’ taxonomy or their International Union for Conservation of Nature Red List category. Identifying poorly represented species and where they occur highlights shortfalls where expansion of the network could bring conservation benefits.